(untitled) (PANGEEA, 2025)
The oykonyms (human settlements) from Secaş-table land reflection of the cohabitation of the Romanian population with the German and Hungarian population. The study-region includes the Secaş-table land in the middle of Transilvania, that extend over 50 km in length and have a maximum width of 40 km, extending around 1100 km2. From an administrative viewpoint these region falls exclusivly into the Alba county. Without detailing out historical aspects, it should be recalled that Transylvania, a province inhabited by Romanians, was conquered by the Hungarian kings (10th and 11th cc), who proceeded to administering it according to the feudal system of the West. So in mid-12th century, they brought in Saxon colonists who were given a series of previlages on the so-called Fondus regius (the Royal Domain). As a result of this cohabitation, the Secaş-table land are rich in toponyms, including 63 oikonyms (human settlements), from this 32% are the Romanian origin, 23% are Hungarian origin and 8% the German origin. Key-words: toponimy, environment, hystorical events, linguistic origin, Secaş-table land.